Formulasi dan Uji Stabilitas Fisik Krim Ekstrak Daun Jati (Tectona grandis L.) Sebagai Pewarna Rambut - Arini Syarifah; Azhara Regita Vegy Miranda; Arif Budiman (Fakultas Farmasi Universitas Setia Budi, 2020)
Para-Phenylenediamine is a synthetic hair dye that is widely used in hair dye products and has very strong sensitizer that can cause severe allergic reactions. Solution of this problem are the development of hair dye formulations with active ingredients obtained from teak leaves. Teak leaves contains anthocyanin which acts as a coloring agent. Teak leaves were extracted using the ultrasound assisted extraction method with ethanol 70% with a frequency in 40 kHz for 30 minutes then evaporated using a rotary evaporator. Formulation of hair dye using concentration extract : 10 (F1); 12.5 (F2); and 15% (F3). Physical evaluation of cream hair dye are organoleptic, homogeneity, pH, viscosity and diffusion test. Stability test using cycling test method. Teak leaf extract cream gives a reddish brown color to the hair. Homogeneity test show all formulas are homogeneous. pH test result of each formula was 6.297 ± 0.118 (F1), 6.770 ± 0.010 (F2) and 5.917 ± 0.045 (F3). The viscosity value of each formula was 11,400 ± 268,514 (F1), 11,463 ± 501,232 (F2) and 11,687 ± 283,078 cPs (F3). Spreadability test showed long spreadability of each formula was 5.326 ± 0.303 (F1), 5,072 ± 0.760 (F2), and 5,050 ± 0.092 cm (F3). The stability test results show that F3 is the most stable formula.